Auditory Long-Range Parvalbumin Cortico-Striatal Neurons - Bertero, Alice; Zurita, Hector; Normandin, Marc; Apicella, Alfonso Junior (Frontiers in Neural Circuits, 2020)
Previous studies have shown that cortico-striatal pathways link auditory signal to action selection and reward-learning behavior through excitatory projections. Only recently it has been demonstrated that long-range GABAergic cortico-striatal somatostatin-expressing neurons in the auditory cortex project to the dorsal striatum, and functionally inhibit the main projecting neuronal population, the spiny projecting neuron. Here we tested the hypothesis that parvalbumin-expressing neurons of the auditory cortex can also send long-range projections to the auditory striatum. In order to address this fundamental question, we took advantage of viral and non-viral anatomical tracing approaches to ide-tify cortico-striatal parvalbumin neurons (CS-Parv inhibitory projections → auditory striatum). Here, we describe their anatomical distribution in the auditory cortex, and determine the anatomical and electro-physiological properties of layer 5 CS-Parv. We also analyzed their characteristic voltage-dependent membrane potential gamma oscillation, showing that they are generated by intrinsic membrane mechanisms and are able to trigger intermittent and irregular bursts (stuttering) of action potential in response to steps of depolarizing current pulses.